2021
DOI: 10.15605/jafes.036.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Risk Factors leading to Diabetes Mellitus among the Young (YOD) from the 8th Philippine National Nutrition Survey

Abstract: Objectives. This study looked into the prevalence of diabetes mellitus (DM) and risks for cardiovascular and metabolic diseases among young adults with diabetes (age 20-44 years old, YOD) and late-onset DM (≥45 years old, LOD) in Filipinos.Methodology. Weighted data from 546,580 adults with DM from the 8 th Philippine National Nutrition and Health Survey (NNHeS) were utilized. Differences in sociodemographic, anthropometric, clinical profiles and metabolic risks were compared between YOD and LOD.Results. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Results from a longitudinal study supporting the healthy immigrant hypothesis found that Filipino migrants self-reported significantly better health, less depression, larger hip circumference, and lower waist-to-hip ratio than residents in the Philippines ( 18 ). Our results align with the hypothesis that increasing BMI and other lifestyle behaviors may be responsible for the rising type 2 diabetes rates and agrees with findings among women with Filipino ancestry ( 31 ), young adults in the Philippines ( 32 ), Japanese migrants to the US ( 33 ), and a review of worldwide migrant populations ( 34 ). Once Filipino immigrants acculturate to the US, they may start to consume a more American diet and eat fewer Filipino foods ( 13 ), in addition to adopting other disease risk factors of the host country, as is often described in migration studies ( 17 , 21 ).…”
Section: Discussionsupporting
confidence: 90%
“…Results from a longitudinal study supporting the healthy immigrant hypothesis found that Filipino migrants self-reported significantly better health, less depression, larger hip circumference, and lower waist-to-hip ratio than residents in the Philippines ( 18 ). Our results align with the hypothesis that increasing BMI and other lifestyle behaviors may be responsible for the rising type 2 diabetes rates and agrees with findings among women with Filipino ancestry ( 31 ), young adults in the Philippines ( 32 ), Japanese migrants to the US ( 33 ), and a review of worldwide migrant populations ( 34 ). Once Filipino immigrants acculturate to the US, they may start to consume a more American diet and eat fewer Filipino foods ( 13 ), in addition to adopting other disease risk factors of the host country, as is often described in migration studies ( 17 , 21 ).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, results were categorised according to all age groups, with those aged over 45 years were identified as a high-risk population with DM. 27 …”
Section: Methodsmentioning
confidence: 99%